Serum vitamin E concentration and osmotic fragility in female long-distance runners - Tomten, S. E.; Hostmark, A. T. (Journal of Sports Sciences, 2009)
The objective of this study was to assess the nutritional adequacy of sub-elite runners with irregular menstrual function (n = 10) and that of a comparable group of runners with regular menstrual function (n = 10), with a special focus on vitamin E. Based on 3 days' records of weighed dietary intake, the mean energy intakes of micro- and macronutrients were estimated. Both estimated daily energy intake (irregular: 9.9 ± 0.4 MJ; regular: 12.2 ± 0.7 MJ; mean ± sx) and intake of dietary fat (irregular: 61 ± 6 g; regular: 98 ± 12 g) were lower in athletes with irregular menstrual function than in athletes with regular menstrual function (P = 0.01). Estimated intake of vitamin E was below recommended values in both groups. Serum concentrations of -tocopherol were used to evaluate vitamin E status, which were normal in athletes with regular menstrual function (27.3± 3.6 µmol/l) but below normal values in athletes with irregular menstrual function (15.7 ± 0.8 µmol/l; P = 0.01). Furthermore, post-exercise osmotic fragility in red blood cells was inversely related to resting -tocopherol concentrations. Our results indicate that irregular menstrual function in athletes on a low-fat diet is associated with low concentrations of circulating -tocopherol, rendering the red blood cells more susceptible to haemolysis in connection with physical activity